Floral Distribution of a Sub-Bituminous Coal Dumpsite in Enugu, Nigeria - Nsa, Imade Y.; Oyebanji, Oyetola O.; Igbinigie, Eric E.; Odunsi, Ayodeji A. (Frontiers in Ecology and Evolution, 2021)
The remnant floral diversity of a naturally reclaimed area proximal to an abandoned mine was assessed. The coal mine site, the Incident zone (IZ) and an unsullied site, the Control zone (CZ), were sampled. Using a 5 m2 quadrat, the floristic composition was determined by the occurrence, distribution analysis, and species diversity indices. The study revealed a degraded vegetation type and recorded a total of 60 species, 53 genera and 27 families. Both the IZ and CZ shared 26.67% species similarity, while 36.67% are were unique to each zone. Five species were dominant (Ageratum conyzoides, Panicum maximum, Calopogonium mucunoides, Chromolaena odorata). While the dominant genera vary between IZ (Borreria, Dioscorea, Ipomoea, and Phyllanthus) and CZ (Desmodium, Euphorbia, and Ipomoea), Asteraceae and Poaceae were the dominant families in both zones. Forbs were the most dominant life forms in both zones; Cyclosorus sp. and Adiantum sp. were only found on the IZ, whereas, Kyllinga erecta and Mariscus alternifolius were exclusive to the CZ. Our results reflect that species composition and vegetation paradigm in the study area could be influenced by coal mining, farming, infrastructural installations and climate. Hence, we suggest future studies to investigate how the species adapt to the environment. Although most of the species encountered belonged to lower-risk conservation, the conservation of the species to this area is imperative.